Progress in the development of paper-based diagnostics for low-resource point-of-care settings. (November 2013) - Byrnes, Samantha; Thiessen, Gregory; Fu, Elain
This Review focuses on recent work in the field of paper microfluidics that specifically addresses the goal of translating the multistep processes that are characteristic of gold-standard laboratory tests to low-resource point-of-care settings. A major challenge is to implement multistep processes with the robust fluid control required to achieve the necessary sensitivity and specificity of a given application in a user-friendly package that minimizes equipment. We review key work in the areas of fluidic controls for automation in paper-based devices, readout methods that minimize dedicated equipment, and power and heating methods that are compatible with low-resource point-of-care settings. We also highlight a focused set of recent applications and discuss future challenges.